The Effect of Directed Reading Thinking Activity (DRTA) Method on Students’ Reading Comprehension for State Islamic Senior High School - Hasan, Abdullah (Journal of English and Arabic Language Teaching, 2017)
This study aims to find out the effect of using Directed Reading Thinking Activity (DRTA) Method on students’ reading comprehension. A quasi-experimental design was used with pre-test and post-test non-equivalent control group design. The number of participants was 63 students divided into an experimental group (31) and a control group (32) of the students of MAN 1 Pekanbaru. Two research questions and four hypotheses were posed  in this study.  Before conducting the treatment, pretest  was administered, and posttest was administered after the treatment. Independent and dependent (paired) sample t-tests were used to analyze the data. The research finding showed  a  significant  effect  of  using  Directed  Reading  Thinking  Activity  (DRTA) method on students’ reading comprehension. Using DRTA method contributed 72% on students’ reading comprehension, meanwhile the control group using non-DRA method contributed 49%. At last, it can be inferred that DRTA method is suitable to apply in teaching  reading  comprehension  at  State  Islamic  Senior  High  School  (MAN)  1 Pekanbaru.